Lanthanide Luminescence Modulation by Cation–π Interaction in a Bioinspired Scaffold: Selective Detection of Copper(I). Issue 39 (29th July 2015) - Isaac, Manon; Denisov, Sergey A.; Roux, Amandine; Imbert, Daniel; Jonusauskas, Gediminas; McClenaghan, Nathan D.; Sénèque, Olivier
Abstract: A prototype luminescent turn‐on probe for Cu + (and Ag + ) is described, harnessing a selective binding site (log Kass =9.4 and 7.3 for Cu + and Ag +, respectively) based on the coordinating environment of the bacterial metallo‐chaperone CusF, integrated with a terbium‐ion‐signaling moiety. Cation–π interactions were shown to enhance tryptophan triplet population, which subsequently sensitized, on the microsecond timescale, the long‐lived terbium emission, offering a novel approach in bioinspired chemosensor design. Abstract : New strategy : A selective probe for Cu I among physiological cations is described, which harnesses a 3D arrangement of four amino acids as the binding site, inspired by the metallo‐chaperone CusF. Luminescence signal transduction results from modulation of the antenna effect through a cation–π interaction that increases intersystem crossing and subsequent lanthanide sensitization.